Doppler flowmetry of ophthalmic arteries for prediction of pre-eclampsia - Aquino,Larissa Oliveira de (2014)
Background: central nervous system (CNS) hyperperfusion is one of the events that constitute the pathophysiological basis for the clinical manifestations and complications of pre-eclampsia (PE). Detecting the increased flow in the CNS through Doppler flowmetry of the ophthalmic artery might precede the clinical onset of PE and could be used as a marker for subsequent development of PE. Objective: to evaluate the ophthalmic artery resistive index (OARI) values in the second trimester of pregnancy for prediction of the clinical manifestations of PE. Objective: to evaluate the ophthalmic artery resistive index (OARI) values in the second trimester of pregnancy for prediction of the clinical manifestations of PE. Methods: a total of 73 patients with risk factors for the development of PE were selected from the prenatal service at the HC-UFMG. They were submitted to ophthalmic artery Doppler flowmetry between 24 and 28 weeks of pregnancy and monitored until the end of the pregnancy to verify the occurrence of PE. ROC curves were created to determine the predictive characteristics of the OARI. Results: fourteen of the patients selected developed PE and 59 remained normotensive until the postpartum period. Patients with subsequent development of PE presented OARI values lower than patients that remained normotensive (0.682±0.028 X 0.700±0.029, p=0.044). Considering the development of PE as an outcome, the area under the OARI curve was 0.694 (CI 0.543 to 0.845), with no points obtaining good values of sensitivity or specificity. Conclusion: Doppler flowmetry of ophthalmic arteries between 24 and 28 weeks of pregnancy did not present itself as a good exam for predicting PE.